2005
DOI: 10.1002/jat.1015
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the binding of cholera toxin to ganglioside GM1 immobilized onto microtitre plates

Abstract: Ganglioside GM1 is the receptor for cholera toxin on cell surfaces, and the binding of cholera toxin to GM1 immobilized on microtitre plates has been reported previously by several authors as an assay for the toxin (GM1-ELISA). This assay has been examined in detail. Results were independent of the adsorption solvent for GM1 (methanol or phosphate-buffered saline), the pH of aqueous solvents (7.4-10.2) and the temperature (4-37 degrees C). High and near-maximal rates of absorbance change in the assay were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 21 publications
1
36
0
Order By: Relevance
“…The relationship between Ctx-HRP concentration and peroxide-induced colour formation is sigmoidal, a result in agreement with other studies. 49,50 Furthermore, the concentration of Ctx-HRP corresponding to half-maximal binding was estimated to be 15 ng mL À1 or 0.153 nM. Other important developments include the incubation period between potential inhibitors and Ctx, which was set at 2 h before addition to the plate to maximise interactions between sugar and toxin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between Ctx-HRP concentration and peroxide-induced colour formation is sigmoidal, a result in agreement with other studies. 49,50 Furthermore, the concentration of Ctx-HRP corresponding to half-maximal binding was estimated to be 15 ng mL À1 or 0.153 nM. Other important developments include the incubation period between potential inhibitors and Ctx, which was set at 2 h before addition to the plate to maximise interactions between sugar and toxin.…”
Section: Discussionmentioning
confidence: 99%
“…A further 2-h incubation 'on plate' was chosen because time-dependency experiments have shown that the maximum binding of Ctx to GM1 is reached in 90 min. 49 Bound/uninhibited Ctx-HRP was developed with 3,3 0 ,5,5 0 -tetramethylbenzidine (TMB) rather than o-phenylenediamine free base as the peroxidase substrate because of its sensitivity in detecting low concentrations of Ctx-HRP. The statistical mean of each set of absorbance readings was used to calculate the concentration of Ctx-HRP that was not inhibited, and consequently able to bind to the immobilised GM1 surface.…”
Section: Discussionmentioning
confidence: 99%
“…The assembled pentamer is capable of binding five ganglioside GM1 receptors at once (Merritt et al 1994;, 1998. The CTB binds very tightly to GM1, with reported Kd values in the range of 5 pM to 1 nM based on surface plasmon resonance and oncell binding measurements (Cuatrecasas 1973;Kuziemko et al 1996;MacKenzie et al 1997;Dawson 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Several methods for supported lipid layer formation onto hydrophilic surfaces are described in the literature, namely, Langmuir-Blodgett transfer [8,9], spin coating [16], vesicle fusion [3,4,8,[10][11][12]17], and deposition from mixed micelles [5,6,13]. The methods to form the lipid layers selected in this study were vesicle fusion, since it was found to be the most common method, adsorption of mixed micelles, due to the fact that little work has been devoted to their use, and the so called hydration method (deposition from solvent), which is normally employed in the ELISA assays [18,19]. A comparison between different methods of preparing phospholipid surfaces was reported by Malmsten [20].…”
Section: Introductionmentioning
confidence: 99%